DUA KASUS MULTIPEL SKLEROSIS DENGAN TIPE YANG BERBEDA DI RSUP M DJAMIL PADANG - Yuri Haiga,* Dian Ayu Hamama Pitra* Meiti Frida* (Neurona Majalah Kedokteran Neuro Sains, 2016)
SCLEROSIS MS IS A NEURODEGENERATIVE DISEASE WITH MULTIPLE DEMYELINATING LESIONS RARELY FOUND IN THE TROPICAL REGION THUS FAR THERE IS NO EPIDEMIOLOGICAL DATA OF MS IN INDONESIA WE REPORTED TWO MULTIPLE SCLEROSIS PATIENTS FROM M DJAMIL HOSPITAL PADANG